Uncovering Scientific Misconduct: The Impact of Intellectual Dishonesty on Occupational Health Studies of Leukemia and Benzene Exposure at The Workplace - Monica Cynthia Dewi (The Indonesian Journal of Community and Occupational Medicine, 2024)
Introductions: There are several unscrupulous companies using benzene in the industry that have taken various actions to manipulate the actual health impacts that can occur due to exposure to benzene, resulting in the dissemination of misleading information to the public. This review aims to compile and analyze scientific misconduct, exploring how this action has impacted public health policies and worker safety regulations over the years and their efforts throughout the years to prevent the right action.Methods : A literature review was conducted to explore instances of scientific misconduct in occupational health studies related to leukemia due to benzene exposure in October 2024. The sources were taken from Google Scholar and PubMed. From the entire search, 2 relevant studies and 1 report were reviewed.Results: Globally, companies using benzene which had manipulated data have contributed to significant delays in implementing regulations regarding benzene exposure. Many scientific errors related to benzene exposure have been identified, especially in the United States. This includes manipulating data from the 1950s to 1970s, specifically regarding the health impacts of benzene exposure and its relationship to the incidence of leukemia. Scientific misconduct causes significant delays in the implementation of necessary regulations.Conclusions: The industry that uses benzene has intentionally manipulated scientific data to shape corporate and public perceptions, causing prolonged production and use of benzene. This has involved the use of research and manipulation of research data to obscure the true results that benzene causes leukemia.